A Low Reabsorbing Luminescent Solar Concentrator Employing π‐Conjugated Polymers. Issue 3 (24th November 2015) - Gutierrez, Gregory D.; Coropceanu, Igor; Bawendi, Moungi G.; Swager, Timothy M.
Abstract : A highly efficient thin‐film luminescent solar concentrator (LSC) utilizing two π‐conjugated polymers as antennae for small amounts of the valued perylene bisimide Lumogen F Red 305 is presented. The LSC exhibits high photoluminescence quantum yield, low reabsorption, and relatively low refractive indices for waveguide matching. A Monte Carlo simulation predicts the LSC to possess exceptionally high optical efficiencies on large scales.